2007
DOI: 10.1007/s10584-006-9182-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and interannual variability of carbon dioxide and water balances of a grassland

Abstract: There is great international concern over the increase of atmospheric carbon dioxide and its effect on vegetation and climate, and vice versa. Many studies on this issue are based on climate model calculations or indirect satellite observations. In contrast we present a 12-year study (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005) on the net ecosystem exchange of carbon dioxide (NEE ) and precipitation surplus (i.e., precipitation-evaporation) of a grassland area in the centre of the N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
(35 reference statements)
2
27
0
Order By: Relevance
“…Site-level studies have shown that the annual amount and timing of precipitation is the major factor affecting gross primary productivity and respiration (Xu and Baldocchi, 2004;Jacobs et al, 2007;Craine et al, 2012), and thus, the NEP in the arid and semi-arid ecosystems. In our study, we found the northern China's grasslands were sensitive to precipitation.…”
Section: Sensitivity Of Northern China's Grasslands To Precipitation mentioning
confidence: 99%
“…Site-level studies have shown that the annual amount and timing of precipitation is the major factor affecting gross primary productivity and respiration (Xu and Baldocchi, 2004;Jacobs et al, 2007;Craine et al, 2012), and thus, the NEP in the arid and semi-arid ecosystems. In our study, we found the northern China's grasslands were sensitive to precipitation.…”
Section: Sensitivity Of Northern China's Grasslands To Precipitation mentioning
confidence: 99%
“…Some established grasslands are believed to have a net uptake of atmospheric CO 2 at annual timescales (Byrne et al, 2007;Jacobs et al, 2007), but temperate, managed grasslands tend to have a net emission of CO 2 over the winter months (Jaksič et al, 2006;. A growing body of evidence suggests that long-term carbon sequestration in grassland is largely controlled by management practices (Soussana et al, 2004;Ammann et al, 2007;Skinner, 2008;Wohlfahrt et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The eddy covariance (EC) technique has become well-established as a method of measuring surface-atmosphere fluxes of energy and trace gases, with several sites now observing continuously for five years or longer (Jacobs et al, 2007;Wohlfahrt et al, 2008;Haslwanter et al, 2009). The technique is suitable for measuring fluxes in the area adjacent to the sensor, but extended networks of flux observation sites together with satellite remote sensing have helped to address the issue of quantifying CO 2 exchange at the continental scale (Xiao et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…• C, E a the ecosystem sensitivity coeafficient in K, R * the universal gas constant, and T s the upper soil layer temperature in K. In contrast to Jacobs et al (2007a) and for practicality, we assume here no dependance of soil respiration on water stress. We use an R 10 of 0.08 mg CO 2 m −2 s −1 , and an E a of 53 kJ kmol −1 , two reasonable values measured over grassland sites in the Netherlands (Jacobs et al, 2007b).…”
Section: Soil Respiration and Resulting Net Ecosystem Exchangementioning
confidence: 99%
“…The soil moisture index (SMI, see Eq. 3.13) obtained with MXL-GECROS is very low, which suggests a heavy drought situation that was not observed: Jacobs et al, 2007a).…”
Section: Simulation Setupmentioning
confidence: 90%